PENGARUH PROGRAM E-COMMERCE DAN KEMAMPUAN USAHA TERHADAP KEMANDIRIAN INDUSTRI KECIL DAN MENENGAH DI KOTA DENPASAR - sutrisno, mey linda anggraeni; Sri Budhi, made kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 8 No 9 (2019): Vol. 8, No.9, September 2019, pp (1947-2194), 2019)
The small and medium-sized enterprise sectors or Industri Kecil dan Menengah (IKM) have proved that they can contribute in developing economic growth movement. Therefore, the government continuously strives for the development of these sectors through various empowering programs. The government of Denpasar city conducts empowering programs, known as E-commerce program, intended for the businessman of IKM. E-commerce is the form of government’s effort to realize IKM with the basis of technology utilization as the tool of promotion and market transaction. The government provides website for the members who join this program to sell their goods. The aims of this research are: (1) to analyze the influence of E-commerce program and Business Ability simultaneously toward the Business Idependence from the IKM’s businessman in Denpasar, (2) to analyze the influence of E-commerce program and Business Ability partially toward the Business independence. With the technique of analysis applied in this research, Regression with Modelling Partial Least Square (PLS), the result found are E-commerce program (X1) and Business Ability (X2) had simultaneously and significant influence to Business Independence and E-Commerce Program has positive and significant influence toward Business Independence, while Business Ability has positive influence and is not significant influence toward Business Independence.